Efektivitas Peraturan Daerah Nomor 03 Tahun 2012 tentang Pengelolaan Sampah di Kabupaten Probolinggo terhadap Kesadaran Masyarakat dalam Pengembangan Bank Sampah - Al Zahra, Fatimah; Wulandari, Fitria; Hasanah, Muflahatul; Hasanah, Nur (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2021)
The increasing population lead to an increase in the volume, type, and characteristics of waste. Waste has become a global problem so that its management needs to be carried out in a comprehensive and integrated manner from upstream to downstream. A little mistakes in waste management will have an impact on environmental pollution and even lead to natural disasters. This research is a study related to its special environmental management regarding community empowerment through the development of waste bank in Probolinggo city. This research uses normative emphirical research. The normative emphirical research is a combination of normative legal approach with the addition of various empirical elements. Due to this research is related to community empowerment in developing garbage bank in managing environment. Subjects in this study are regulatory regulations relating to environmental management, especially the management of waste bank in the Probolinggo city. In this study, the object is the Local Regulation number 03 of 2013 on Waste Management. From the results of the study concluded that Regional Regulation number 03 of 2013 on waste management in the Probolinggo city has provided fresh wind to the development of waste bank in Probolinggo city which is also warmly welcomed by the Probolinggo city society to be aware of hygiene by changing the paradigm of society by gathering, transport, waste. Now the paradigm is transformed into saving innovation through waste bank by reusing existing waste with 3R (Reduce, Reuse, Recycle) Program.